A Modal Ontology of Imagination - Julia de Boer (Aesthetic Investigations)
Everyday aesthetics has been accused of being ontologically and systematically juvenile for a variety of reasons, such as the rejection of some major claims of Kantian aesthetics, its relative newness, its disparate methodologies, and the theoretical and ethical difficulties of outlining a systematic apparatus without reimposing rationalist and colonial perspectives. While it is untrue that everyday aesthetics as a new sub-discipline lacks systematic rigour, another ontology of the everyday will be introduced here. Calvin Seerveld’s aesthetic theory will be outlined and then offered as a resource for understanding the constitutive role imagination plays in analytical and other kinds of thinking. His notion of ‘allusivity’ as the common quality of all aesthetic expression suggests that art, craft, design, and everyday aesthetic appreciation all emerge from the same subjective function of imaginative ‘nuance’. Additionally, his thought comes from within an established tradition of modal ontology begun by 20th century Dutch Continental philosopher Herman Dooyeweerd.